Fiscal Devaluation in a Monetary Union - Engler, Philipp (IMF Working Papers; Working Paper, 2014)
Using a DSGE model calibrated to the euro area, we analyze the international effects of a fiscal devaluation (FD) implemented as a revenue-neutral shift from employer's social contributions to the Value Added Tax. We find that a FD in 'Southern European countries' has a strong positive effect on output, but mild effects on the trade balance and the real exchange rate. Since the benefits of a FD are small relative to the divergence in competitiveness, it is best addressed through structural reforms.